Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Find $\dfrac{d}{dx}(\cos x)$

I know the answer is $-\sin x$ only by process of elimination. I can find solution graphically but I need to know algebraically. Here is my proof so far.
$\begin{align*} \dfrac{d}{dx}\cos x=\lim_{h\to 0}\dfrac{\cos (x+h)-\cos x}{h} &=\lim_{h\to 0}\dfrac{\cos x\cos h-\sin x\sin h-\cos x}{h} \end{align*}$

And that's where I end up and I have no clue where to go from here. Can someone please give me the next step but not the complete answer.

share|improve this question
1  
Can you explain in what sense you "need to know algebraically"? –  Hurkyl Oct 6 '12 at 3:45
    
More like I just need to know how to prove it. –  Austin Broussard Oct 6 '12 at 16:30

4 Answers 4

up vote 3 down vote accepted

You need to know how to evaluate the following limits: $$ \lim_{h \rightarrow 0} \frac{ \cos{h} - 1}{h}, \quad \lim_{h \rightarrow 0} \frac{ \sin{h}}{h}$$

share|improve this answer

$$\cos h -1=\frac{(\cos h -1)(\cos h+1)}{\cos h +1}$$

Alternately, use the fact that $$\cos 2t=\cos^2 t-\sin^2 t=2\cos^2 t-1=1-2\sin^2 t.$$

share|improve this answer

If you know $d \sin x / dx$, then relate $\cos$ to $\sin$.

Or find some other way to combine things to relate what you know to what you don't know (or what you don't know to itself). One mildly amusing approach is

$$ \frac{d}{dx} \left( \sin^2 x + \cos^2 x \right) $$

share|improve this answer

sorry i cant and i dont know how to write math symbols here hope u understand like that.

lim [ cos(x + h) - cos(x) ] / h h -> 0

lim [ cos(x)cos(h) - sin(x)sin(h) - cos(x) ] / h h -> 0

lim [ cos(x)cos(h) - cos(x) - sin(x)sin(h) ] / h h -> 0

lim [ cos(x) [ cos(h) - 1 ] - sin(x)sin(h) ] / h h -> 0

lim [ cos(x) [ cos(h) - 1 ]/h - [sin(x)sin(h)]/h h -> 0

lim [ cos(x) [cos(h) - 1]/h ] - lim sin(x)sin(h)/h h -> 0 . . . . . . . . . . . . . . . . . . h -> 0

Factor cos(x) from the first limit, and sin(x) from the second limit.

cos(x) lim [ cos(h) - 1 ]/h - sin(x) lim sin(h)/h . . . . . . h -> 0 . . . . . . . . . . . . . . . . . h -> 0

We need foreknowledge of trig limits to realize that lim [ cos(h) - 1 ]/h = 0, and h -> 0 lim sin(h)/h = 1 h -> 0

The above then becomes

cos(x) (0) - sin(x)(1) 0 - sin(x)

     or

cos x*cos h - sin x*sin h -cos x)/h As h is tending to zero..... cos h =1 =(cos x - cos x -sin x*sin h)/h = -sin x*(sin h)/h sin h/h=1 = - sin x

-sin(x)

share|improve this answer
1  
IMO, simply writing a complete answer is usually a poor way to help someone learn to solve problems. Furthermore, the questioner specifically asked not to be given one. –  Hurkyl Oct 6 '12 at 19:24

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.